Enhancement of Loperamide Dissolution Rate by Liquisolid Compact Technique - Kambham Venkateswarlu; Jami Komala Preethi; Kothapalli Bonnoth Chandrasekhar (Tabriz University of Medical Sciences, 2016)
Objective: The aim of present study was to improve the dissolution rate the poorly soluble drug Loperamide (LPM) by liquisolid compact technique. Methods: Liquisolid compacts of LPM were prepared using Propylene glycol (PG) as a solvent, Avicel pH 102 as carrier, Aerosil as coating material and Sodium Starch Glycolate (SSG) as superdisintegrant. Interactions between the drug and excipients were examined by Fourier Transform Infrared (FTIR) spectroscopy. The dissolution studies for LPM liquisolid formulation, marketed product and pure drug were carried out in pH 1.2 HCl buffer as dissolution media. Results: Results confirmed the absence of chemical interactions between the drug and excipients. From the solubility studies, it was observed the LPM was highly soluble in PG thereby it was selected as a solvent. The dissolution efficiency of LPM at 15 min was increased from 9.99 % for pure drug and 54.57% for marketed product to 86.81% for the tablets prepared by liquisolid compact technique. Stability studies showed no significant change in percent cumulative drug release, hardness, disintegration time, friability and drug content for 3 months. Conclusion: Formulation F2 showed significant increase in dissolution rate compared to the marketed product at pH 1.2 where LPM is largely absorbed. Around 90% of the drug was released from F2 in 30 min compared to the marketed product and it might be due to the increased wetting and surface area of the particles. Hence, the liquisolid compact technique appears to be a promising approach for improving the dissolution rate of poorly soluble drug.